Activation of Water‐Splitting Photocatalysts by Loading with Ultrafine Rh–Cr Mixed‐Oxide Cocatalyst Nanoparticles. Issue 18 (6th March 2020) - Kurashige, Wataru; Mori, Yutaro; Ozaki, Shuhei; Kawachi, Masanobu; Hossain, Sakiat; Kawawaki, Tokuhisa; Shearer, Cameron J.; Iwase, Akihide; Metha, Gregory F.; Yamazoe, Seiji; Kudo, Akihiko; Negishi, Yuichi
Abstract: The activity of many water‐splitting photocatalysts could be improved by the use of Rh III –Cr III mixed oxide (Rh2− x Cr x O3 ) particles as cocatalysts. Although further improvement of water‐splitting activity could be achieved if the size of the Rh2− x Cr x O3 particles was decreased further, it is difficult to load ultrafine (<2 nm) Rh2− x Cr x O3 particles onto a photocatalyst by using conventional loading methods. In this study, a new loading method was successfully established and was used to load Rh2− x Cr x O3 particles with a size of approximately 1.3 nm and a narrow size distribution onto a BaLa4 Ti4 O15 photocatalyst. The obtained photocatalyst exhibited an apparent quantum yield of 16 %, which is the highest achieved for BaLa4 Ti4 O15 to date. Thus, the developed loading technique of Rh2− x Cr x O3 particles is extremely effective at improving the activity of the water‐splitting photocatalyst BaLa4 Ti4 O15 . This method is expected to be extended to other advanced water‐splitting photocatalysts to achieve higher quantum yields. Abstract : Rh2− x Cr x O3 particles with a size of approximately 1.3 nm were loaded onto a BaLa4 Ti4 O15 photocatalyst. The photocatalyst exhibited the highest quantum yield reported for BaLa4 Ti4 O15 . The developed preparation technique of Rh2− x Cr x O3 particles is also expected to improve the activity of other advanced water‐splitting photocatalysts. SG=glutathionate.